Solve the system using substitution.


y minus 2 x equals 3.
3 x minus 2 y equals 5.
(1 point)
Responses

the ordered pair (negative one-half, 2)
Image with alt text: the ordered pair (negative one-half, 2)

the ordered pair (2, 7)
Image with alt text: the ordered pair (2, 7)

the ordered pair (negative 8, negative 13)
Image with alt text: the ordered pair (negative 8, negative 13)

the ordered pair (negative 11, negative 19)

1 answer

To solve the system using substitution, we need to solve one equation for one variable and substitute that expression into the second equation.

From the first equation, we have:
y - 2x = 3
Rearranging, we get:
y = 3 + 2x

Now substitute this expression for y in the second equation:
3x - 2(3 + 2x) = 5
Distribute:
3x - 6 - 4x = 5
Combine like terms:
-x - 6 = 5
Add 6 to both sides:
-x = 11
Divide by -1:
x = -11

Substitute this value of x back into the expression for y:
y = 3 + 2(-11)
y = 3 - 22
y = -19

Therefore, the ordered pair is (-11, -19), which is not listed as a response option.